Association of Serum Complement C1q and C3 Level with Age-Related Macular Degeneration in Women - Ma Y; Ding X; Shao M; Qiu Y; Li S; Cao W; Xu G (Dove Medical Press, 2022)
Yingbo Ma,1,* Xueqing Ding,1,* Mingxi Shao,1 Yichao Qiu,1 Shengjie Li,1 Wenjun Cao,1,2 Gezhi Xu2- 4 1Department of Clinical Laboratory, Eye and ENT Hospital of Fudan University, Shanghai, People's Republic of China; 2Department of Ophthalmology, Eye and ENT Hospital of Fudan University, Shanghai, People's Republic of China; 3Shanghai Key Laboratory of Visual Impairment and Restoration, Fudan University, Shanghai, People's Republic of China; 4NHC Key Laboratory of Myopia, Fudan University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Shengjie Li; Wenjun CaoDepartment of Clinical Laboratory, Eye and ENT Hospital of Fudan University, Fenyang Road 83th, Xuhui District, Shanghai, People's Republic of ChinaTel +86-21-64377134Email lishengjie6363020@163.com; 18917785088@163.comPurpose: To investigate the association between serum complement components and age-related macular degeneration (AMD).Patients and Methods: A total of 118 AMD patients and age- and sex-matched 106 control subjects were included. Demographic data and the level of serum complement component (C)1q, C3 and C4 were evaluated. Based on sex, the subjects were stratified into male and female subgroups.Results: The level of C1q (226.31± 45.33mg/dL) was significantly higher and C3 (121.14± 15.76mg/dL) was significantly lower than that in control group (200.03± 38.54mg/dL) (128.42± 19.81mg/dL) in the female AMD patients (p = 0.005, p = 0.045). Logistic regression showed that increased C1q (OR = 1.132, p = 0.016) and decreased C3 (OR = 0.960, p = 0.048) were independent risk factors for female AMD patients. No statistical significance was observed in the male.Conclusion: Increased C1q and decreased C3 were associated with increased risk of AMD, suggesting that the complement classical pathway probably be involved in AMD, especially in female.Keywords: macular degeneration, complement classical pathway, complement component, peripheral blood, case-control study